Wheat Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Shoup, Douglas; Martin, Kent L. (My University, 2009)
This publication projects a budget that reflects expected income and costs based on wheat production in south central Kansas.
MF574_2009_12
Keywords: MF574; Economics; Crops; MF